Novos sistemas de liberação de fármacos à base de xilana - Oliveira, Elquio Eleamen (2010)
The aim of this work was to perform the extraction and characterization of xylan from corn cobs and prepare xylan-based microcapsules. For that purpose, an alkaline extraction of xylan was carried out followed by the polymer characterization regarding its technological properties, such as angle of repose, Hausner factor, density, compressibility and compactability. Also, a low-cost and rapid analytical procedure to identify xylan by means of infrared spectroscopy was studied. Xylan was characterized as a yellowish fine powder with low density and poor flow properties. After the extraction and characterization of the polymer, xylan-based microcapsules were prepared by means of interfacial crosslinking polymerization and their characterization was performed in order to obtain gastroresistant multiparticulate systems. This work involved the most suitable parameters of the preparation of microcapsules as well as the study of the process, scale-up methodology and biological analysis. Magnetic nanoparticles were used as a model system to be encapsulated by the xylan microcapsules. According to the results, xylan-based microcapsules were shown to be resistant to several conditions found along the gastrointestinal tract and they were able to avoid the early degradation of the magnetic nanoparticles